OPTIMIZATION OF THE SCIENTIFIC SEARCH FOR LYME BORRELIOSIS SEVERITY DIAGNOSTICS - Sverstiuk, Andrii; Nykytyuk, Svitlana; Synytska, Vira; Antiuk, Zhanna; Kyrychok, Olexandra (Eastern Ukrainian Medical Journal, 2024)
The article deals with the data of the use of analytical search capabilities for the optimization of the literature sources analysis in the Scopus scientometric database when studying the current state of Lyme borreliosis diagnosis and treatment in children. Methods of examination: analytical requests and assessment were used to investigate the analytical data of the scientific search for Lyme Borreliosis diagnosis. The Scopus scientometric database gives the capabilities to make a relevant search of scientific literature on the studied issues. In particular, to assess the relevance of research on LB in infectious diseases field, the following analytical query was formulated in the Scopus database: (ALL("tick bites") OR ALL("endemic area in lyme borreliosis") OR ALL("questionnaire of parents of children with Lyme disease") OR ALL("affected by ticks") OR ALL("DNA to complex B. burgdorferi s.l. ") OR ALL("B. miyamotoi"). Research results. The use of the Scopus scientometric database optimizes the relevant search of scientific literature by the research topic; total number of papers and comparisons in Cite Score, SIR, SNIP; search results by authors, subject areas, country, among leading scientific institutions, types of publications, and the largest financial sponsors of the research topic. Conclusions: the analytical review of publications on the use of artificial intelligence in medicine, in particular, infectology was presented in the article. The analysis of the papers in the Scopus scientometric database was carried out. The authors with the largest number of papers, taking into account countries and scientific institutions, were presented. Based on the data obtained from the analytical review of literature sources using Scopus, we can conclude that there is a growing scientific interest in the problem of studying the causes of the onset and progression of Lyme borreliosis. Thus, such research is extremely relevant for improving and maintaining patient health.